SISTEM INFORMASI DIGITALISASI DOKUMEN BERBASIS MULTI USER STUDI KASUS DITANKANHUT BANJARBARU: Array (JiTEKH, 2019)
In the era of increasingly rapid technology for paper-based archive management, it needs to be developed in the form of digital archives or electronic documents because it facilitates management and ensures the security of information contained in files from unwanted hazards such as fire, floods, loss of data and so on. At Dinas Pertanian, Perikanan, dan Kehutanan (DITANKANHUT) Banjarbaru management of archives still uses the process of storing manual forms such as being stored in trims or cabinets in this case, it will be difficult in the archive search process if the archive has been stored for a long time and will require a large enough space to store archives office. From these problems an alternative solution can be taken, namely by building a multi-user-based Document Digitization information system to handle the document archiving process digitally and make it easier to rediscover the document.